2013
DOI: 10.1016/j.biomaterials.2012.09.071
|View full text |Cite
|
Sign up to set email alerts
|

Directing cell migration in continuous microchannels by topographical amplification of natural directional persistence

Abstract: Discrete micropatterns on biomaterial surfaces can be used to guide the direction of mammalian cell movement by orienting cell morphology. However, guiding cell assembly in three-dimensional scaffolds remains a challenge. Here we demonstrate that the random motions of motile cells can be rectified within continuous microchannels without chemotactic gradients or fluid flow. Our results show that uniform width microchannels with an overhanging zigzag design can induce polarization of NIH3T3 fibroblasts and human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…The vectors indicated that net motion was isotropic and random on flat surfaces, whereas it was rectified toward the positive y axis on the ratchet pattern. Previous gradient-free strategies relied on cell confinement, either chemical (12)(13)(14)(15) or physical (16)(17)(18). However, here we show that cells on an asymmetric topographical pattern, with no restriction in adhesiveness or physical confinement, moved in the direction imposed by the features of the ratchet itself.…”
Section: Directing Cell Migration With a Ratchet-like Topographymentioning
confidence: 62%
See 3 more Smart Citations
“…The vectors indicated that net motion was isotropic and random on flat surfaces, whereas it was rectified toward the positive y axis on the ratchet pattern. Previous gradient-free strategies relied on cell confinement, either chemical (12)(13)(14)(15) or physical (16)(17)(18). However, here we show that cells on an asymmetric topographical pattern, with no restriction in adhesiveness or physical confinement, moved in the direction imposed by the features of the ratchet itself.…”
Section: Directing Cell Migration With a Ratchet-like Topographymentioning
confidence: 62%
“…Geometrical asymmetries in the pattern design amplified natural differences in lamellipodia activity at the front and the rear of a polarized cell, leading to directed motion (12)(13)(14)(15)17,18). Because we used homogeneous fibronectin coatings and topographical patterns smaller than the cell size and of a moderate height (35), we did not restrict cell migration in any direction.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…5B). 125,126 In cells on a micro-/nano-grooved structure, actin filaments and vinculinrich focal adhesions align with the longer axis of the grooves. This effect causes various cells, such as epithelial, endothelial, glial cells, fibroblasts, osteoblasts, and neutrophils, to align 73,96,120,121 and migrate 4,121,123,124 along the grooves.…”
Section: Cell Migrationmentioning
confidence: 99%